Management of a soft tissue sarcoma diagnosed by biopsy-excision - Delgado, Bolivar; Iraola, Maria L.; Zimmer, Walter; Bounous, Mario (Cirugía del Uruguay, 1977)
In reporting the case of a sarcoma of sort parts, resected without preoperatory diagnosis, possible therapy is discussed, with arguments in favour of early reoperation and broad oncological criteria, even in the case of tumors which are, apparently, hardly malignant and encapsuled. In this paper four cases are described, in which reintervention showed- residual tumors. In the author's opinion, preoperatory diagnosis and systematic anatomopathological analysis are of great value.